IMPLEMENTATION AND EVALUATION OF A DKA ORDER SET IN A PEDIATRIC TERTIARY CARE HOSPITAL: A QUALITY IMPROVEMENT INITIATIVE. (18th May 2018) - Flood, Kayla; Nour, Munier; Cattell, Vicki; Holt, Tayna; Seifert, Blair; Rozdilsky, Janlyn; Inman, Mark
Abstract: BACKGROUND: Diabetic ketoacidosis (DKA) is a common clinical presentation in new and previously diagnosed paediatric patients with type 1 diabetes. In contrast to other Canadian tertiary paediatric hospitals, our center lacked a physician-endorsed evidence-informed care pathway for management of DKA. In the absence of a standardized approach to DKA, variability in patient management and outcomes were observed. This project was a quality improvement initiative that sought to develop and pilot a paediatric DKA order set. OBJECTIVES: Our primary aim was to attain broad clinical uptake of the order set at our tertiary care center over a 12-month period. Secondary aims included improved standard-of-care DKA management: appropriate fluid bolus volume and maintenance rates; initial potassium management; and timely dextrose supplementation. DESIGN/METHODS: A paediatric multidisciplinary collaborative was created to examine evidence for the development and implementation of a DKA order set. Implementation of the order set involved department wide education, targeted end-user education, and quarterly end-user review. A modified plan-do-study-act (PDSA) cycle guided by end-user feedback and early clinical outcomes allowed progressive order set modifications. RESULTS: A retrospective chart review of fifty paediatric patients presenting to our center between April 2014 and September 2016 (pre-implementation) was compared to thirty paediatric patients presenting in DKA during the post-implementation phase (September 2016 – September 2017). There were no statistically significant differences in demographic and clinical characteristics between the groups. We achieved 83% uptake of the order set for patients presenting to our tertiary center and 67% uptake for patients transferred from peripheral centers. Improvements in DKA management included: appropriate intravenous (IV) maintenance fluid rates (20% vs. 48.3%, p=0.008), earlier administration of potassium to IV fluids (66% vs. 93.1%, p=0.006); appropriate potassium chloride dosing (40 mmol/L) to IV fluid (40% vs. 79.3%, p=0.0007) and earlier addition of IV dextrose (67.4% vs. 93.1%, p=0.009 ). No differences in moderate to severe hypokalemia (< 3.0 mmol/L), hypoglycemia (<4.0 mmol/L) or clinically suspected cerebral edema occurred. CONCLUSION: Implementation of a DKA order set in a tertiary hospital required identification of key stakeholders, formation of a multidisciplinary team, and the development of an evaluation process. There was an observed increase in physician order set uptake and DKA management practice improvements. Future goals involve expanding the implementation and evaluation process to regional and remote centers and analyzing the impact on resource utilization.